ORGANIZATIONAL JUSTICE IMPACT ON ORGANIZATIONAL COMMITMENT (In case of company “A”) - G.Uyanga; B.Nomundari; D.Enkh-Otgon, (Journal of Business and Innovation (Бизнес & Инноваци), 2024)
The research examined how organizational justice affects organizational commitment. A total of 250 employees were randomly selected at “A” company in Mongolia. Exploratory factor analysis of the scales was conducted using Microsoft Excel and IBM SPSS Statistics 29.0. The findings indicate all factors of Organizational justice have a rather similar impact on Organizational commitment. There is a slightly stronger correlation between Distributive Justice and Affective Commitment. Procedural justice has a rather strong impact on Continuance Commitment. Both interpersonal and informational justice have a slightly stronger correlation with Affective commitment.